The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/wcc.333
|View full text |Cite
|
Sign up to set email alerts
|

Dual high‐stake emerging technologies: a review of the climate engineering research literature

Abstract: The literature on climate engineering, or geoengineering, covers a wide range of potential methods for solar radiation management or carbon dioxide removal that vary in technical aspects, temporal and spatial scales, potential environmental impacts, and legal, ethical, and governance challenges. This paper presents a comprehensive review of social and natural science papers on this topic since 2006 and listed in SCOPUS and Web of Science. It adds to previous literature reviews by combining analyses of bibliome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 65 publications
(130 reference statements)
0
24
0
2
Order By: Relevance
“…Unlike climate engineering, many other emerging technologies with potentially transformative impacts on society, such as genetically modified organisms, nanotechnology and nuclear power, have significant proportions of promoters and enthusiasts and are rhetorically tightly coupled with progressive and even utopian ideals that climate engineering lacks Hansson 2014a, 2014b). By contrast, a review of peer-reviewed papers on climate engineering published between 2006 and 2013 found that few scientific publications ended in an explicit 'yes' or 'no' to climate engineering, and that less than 2% or the reviewed papers unconditionally advocated deployment (Linnér and Wibeck 2015). A common recommendation in the research literature is that more research and experimentation is needed, though such recommendations are accompanied by calls for caution (Dilling and Hauser 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike climate engineering, many other emerging technologies with potentially transformative impacts on society, such as genetically modified organisms, nanotechnology and nuclear power, have significant proportions of promoters and enthusiasts and are rhetorically tightly coupled with progressive and even utopian ideals that climate engineering lacks Hansson 2014a, 2014b). By contrast, a review of peer-reviewed papers on climate engineering published between 2006 and 2013 found that few scientific publications ended in an explicit 'yes' or 'no' to climate engineering, and that less than 2% or the reviewed papers unconditionally advocated deployment (Linnér and Wibeck 2015). A common recommendation in the research literature is that more research and experimentation is needed, though such recommendations are accompanied by calls for caution (Dilling and Hauser 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Very few hopes of positive side effects, such as increased food production or economic growth, are connected to climate engineering (e.g. Linnér and Wibeck 2015). Expectations for climate engineering can even be described as negative or dystopian: scientists do not promise to succeed in developing climate engineering, and eventual deployment may not even benefit society aside from a chance of negating another major harm (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific and public debate, only few scientists declare any positive side-effects of implementing GE or confirm a better future with GE (Anshelm and Hansson, 2014;Linnér & Wibeck, 2015). One could claim that, despite recent advances in modelling research, the same fundamental issues are still at stake, such as: What views of democracy inform global governance (Heyward and Rayner, 2013;Macnaghten and Szerszynski, 2013)?…”
Section: Discussionmentioning
confidence: 99%
“…Second, is to offer clear and transparent criteria for bounding the issue/field being reviewed and how relevant literature is selected. The WIREs review by Linnér and Wibeck () nicely operationalizes this principle. Third, is to be critical, to pass judgment on a field of published literature or to develop an argument.…”
Section: What Makes a Good Review Article?mentioning
confidence: 99%